Interactive effects of music tempi and intensities on grip strength and subjective affect. (26th December 2017) - Karageorghis, C. I.; Cheek, P.; Simpson, S. D.; Bigliassi, M.
Abstract : Pretask music is widely used by athletes albeit there is scant empirical evidence to support its use. The present study extended a line of work into pretask music by examining the interactive effects of music tempo and intensity (volume) on the performance of a simple motor skill and subjective affect. A 2 × 2 within‐subjects factorial design was employed with an additional no‐music control, the scores from which were used as a covariate. A sample of 52 male athletes ( M age = 26.1 ± 4.8 years) was exposed to five conditions: fast/loud (126 bpm/80 dBA), fast/quiet (126 bpm/70 dBA), slow/loud (87 bpm/80 dBA), slow/quiet (87 bpm/70 dBA) music, and a no‐music control. Dependent variables were grip strength, measured with a handgrip dynamometer, and subjective affect, assessed by use of the Affect Grid. The tempo and intensity components of music had interactive effects for grip strength but only main effects for subjective affect. Fast‐tempo music played at a high intensity yielded the highest grip strength, while fast‐tempo music played at a low‐intensity resulted in much lower grip strength ( M diff. = −1.11 Force kg). For affective valence, there were main effects of tempo and intensity, with fast and loud music yielding the highest scores. For affective arousal, there was no difference between tempi although there was between intensities, with the high‐intensity condition yielding higher scores. The present findings indicate the utility of fast/loud pretask music in enhancing affective valence and arousal in preparation for a simple or gross motor task.